Is the local extinction of Pinna nobilis facilitating Pinna rudis recruitment? - KERSTING, DIEGO KURT; BALLESTEROS, ENRIC (Mediterranean Marine Science, 2021)
Until the late 2010s the spiny fan-mussel Pinna rudis shared habitat in many Mediterranean sites with Mediterranean endemic Pinna nobilis, which dominated in abundance but that has gone locally extinct in most of its distribution area due to a recent widespread disease outbreak. In the Columbretes Islands Marine Reserve (NW Mediterranean) both species coexisted until 2017, when P. nobilis populations completely disappeared. In spring 2021 we revisited 7 permanent plots covering 1,485 m2 that had been previously monitored during the period from 2005 to 2009. We found that although previous studies described P. rudis populations as stable with low recruitment rates, recruitment after 2017 increased in comparison to 2005-2009. At least two cohorts of recruits (~3 and ~1 year in age) were to be found both within the plots as well as in other areas throughout the Columbretes archipelago, colonizing areas previously occupied by P. nobilis. We hypothesize that P. rudis has been benefited by the local extinction of the sibling species P. nobilis, most probably as a result of reduced interspecific competition. The ecological role once played mainly by P. nobilis as the dominant species, might now be taken over by P. rudis, whose populations could grow during the oncoming years.